Diseño de una aplicación para el seguimiento de mantenimientos de equipos biomédicos, y rápida elaboración de hojas de vida y fichas técnicas en una clínica de alta complejidad - González González, Emmanuel (Escuela Colombiana de Ingeniería Julio Garavito, 2020)
As a biomedical practitioner at the Colsubsidio Children's Clinic, you have the responsibility of ensuring compliance with the decrees and resolutions related to the use and provision of medical equipment. For this, the development of an application for Excel using the Visual Basic environment was proposed, in order to quickly form technical sheets and resumes of the teams with their basic information. When building the application, he had difficulties to display the information of computers that do not contain the basic information. However, it was possible to design an application capable of providing the information from the resume and technical file of each team of the Children's Clinic.
Keywords: Equipos biomédicos; Mantenimiento de equipos; Diseño en ingeniería; Aplicaciones móviles; Ingeniería de prototipos; Biomedical equipments; Equipment maintenance; Engineering design; Mobile apps; Prototype engineering